Вы находитесь на странице: 1из 2

1

Partial fraction decomposition of


First, apply this formula: x2 1 = (x + 1)(x 1),

x
x2 1

x
x
=
x2 1
(x + 1)(x 1)
(x+1)+(x1)
,
2

Then we easily obtain x =

x2

x
1

=
=

1
2(x+1)
1
2

we get

1
x+1

(1)

1
2(x1)

(2)

(3)

1
x1

Partial fraction decomposition of

1
x3 +1

Use Sages function, partial fraction(). Type:

sage: (1/(x^3+1)).partial_fraction()
-1/3*(x-2)/(x^2 - x +1) + 1/3/(x+1)

We obtain as follows.
1
3

1
x2

x + 1 x2 x + 1

Partial fraction decomposition of

(4)

x2
x4 +1

This is a little bit tough because Sage cannot solve this directly like:

sage: x^2/(x^4+1).partial_fraction()

Then we transform x4 + 1 into (x2 + 1)2 2x2 as follows:


x4 + 1

=
=

(x2 + 1)2 2x2





x2 + 1 + 2x x2 + 1 2x

Because the decomposition generates 2x, Sage cannot deal with this
matter.

(x2 + 1 + 2x)(x2 + 1 2x) is easy to decompose as follows:


1

sage: (x^2/( (x^2+1+\sqrt(2)*x)*(x^2+1-sqrt(2)*x ).partial_fraction()


-1/4*sqrt(2)*x/(x^2+sqrt(2)*x+19+1/4*sqrt(2)*x/(x^2-sqrt(2)*x+1)

Thus, we obtain:
x
x2
=
x4 + 1
2 2

1
1

2
2
x 2x + 1 x + 2x + 1

(5)